Improving Learning Outcomes in Islamic Cultural History Through the Reciprocal Teaching Model at MTs Nurul Islam Wuluhan Jember - Edi Santoso (Ar-Fachruddin: Pendidikan Agama Islam, 2024)
Research Objective-This study aims to improve student learning outcomes in the subject of Islamic cultural history through the implementation of the reciprocal teaching model at MTs Nurul Islam Wuluhan Jember. Method-The research employed classroom action research conducted in three cycles. Each cycle included planning, action implementation, observation, and reflection stages. Data were collected through observations of student and teacher activities as well as learning outcome tests. Findings-The implementation of the reciprocal teaching model showed a significant improvement in students' learning outcomes. The classical success percentage increased from 42.5% in the pre-test to 57.5% in the first cycle, 85% in the second cycle, and reached 90% in the third cycle. Student activities also demonstrated enhancement, with more active engagement in the learning process. Implications/Limitations- This study reveals that the reciprocal teaching model is effective in improving students' learning outcomes and engagement. However, the research is limited to a single subject and school, making it less generalizable to other contexts. Originality/Value- This study provides practical contributions by adapting the reciprocal teaching method for Islamic cultural history education, offering guidance for teachers in creating more interactive learning environments that foster students' critical thinking skills.